2004
DOI: 10.1177/194589240401800602
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Airflow, Mucociliary Clearance, and Sinus Functioning during Viral Colds: Effects of Allergic Rhinitis and Susceptibility to Recurrent Sinusitis

Abstract: Abnormal nasal airflow and MCC rates seem to be associated with impaired functioning of paranasal sinuses during viral colds and tend to be more common in allergic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
2
23
0
Order By: Relevance
“…Natural as well as experimentally induced viral upper respiratory infections have been associated with prolonged mucociliary clearance as measured by radiolabeled resin beads or dyed saccharin. 163,830 This effect is maximum at 3 days, persists up to 11 days, and is found in a higher proportion of patients with versus without allergy. 163,830 Acute viral infections may also cause cytopathic epithelial damage that may take a number of weeks to resolve.…”
Section: Csf Rhinorrhea 33 Refractory Clear Rhinorrhea May Be a Resumentioning
confidence: 92%
See 2 more Smart Citations
“…Natural as well as experimentally induced viral upper respiratory infections have been associated with prolonged mucociliary clearance as measured by radiolabeled resin beads or dyed saccharin. 163,830 This effect is maximum at 3 days, persists up to 11 days, and is found in a higher proportion of patients with versus without allergy. 163,830 Acute viral infections may also cause cytopathic epithelial damage that may take a number of weeks to resolve.…”
Section: Csf Rhinorrhea 33 Refractory Clear Rhinorrhea May Be a Resumentioning
confidence: 92%
“…[167][168][169] After an infection, resolution of secondary ciliary dysfunction and cytopathic epithelial damage may require weeks. 163,164,[170][171][172] An adverse effect of tobacco smoke on mucociliary clearance in the upper airways in healthy smokers has not been established. 173,174 Evaluation and diagnostic studies in patients with rhinitis History [Summary Statements 35,36] A thorough allergic history remains the best diagnostic tool available.…”
Section: Ciliary Dysfunction Syndromes [Summary Statement 34]mentioning
confidence: 98%
See 1 more Smart Citation
“…Alho confirmed that abnormal nasal airflow is significantly associated with elevated computed tomography scores of the ipsilateral paranasal sinus, further indicating that the impairment in ventilation and drainage in the nasal passages extended into the paranasal sinuses as well [24]. Impairment of sinus function has been considered a key factor in the development of bacterial sinusitis [25].…”
Section: Discussionmentioning
confidence: 87%
“…A study of human subjects in Finland showed that subjects with allergic rhinitis had more severe sinus changes on CT scans during viral URIs, indicating impaired sinus functioning [52]. Another study from this same group compared nasal airflow and mucociliary clearance and their association with sinus functioning during URIs in allergic, sinusitis-susceptible, and control patients [53]. This study demonstrated that a higher proportion of the allergic subjects, but not the sinusitis-susceptible patients, had abnormal nasal airflow and mucociliary clearance values compared with control subjects.…”
Section: Common Inflammatory Responsementioning
confidence: 94%